Estudos botânicos nas ilhas de Maiandeua, Algodoal (Pa). morfologia polínica da vegetação da restinga de Algodoal-Pa - xii- família solanaceae - Serrão, Cleberson Marques (Museu Paraense Emílio Goeldi, 2023)
The Solanaceae family comprises about 3,000 species and 90 genera with a wide distribution, mainly in tropical and subtropical regions of South America. The present work has as main objectives to analyze the pollen grains of the Solanaceae species Schwenchia americana L., Solanum paludosum Moric. and Solanum stramonifolium Jacq. that occur in the restinga of Algodoal-PA and to promote comparison of frequency and pollen type with pollen from vegetation in other ecosystems. To prepare the slides, adult flower buds were collected from exsiccata of the MG herbarium (Museu Paraense Emílio Goeldi-Belém) and later submitted to acetolysis. The pollen grains were measured, described and photomicrographed under light and scanning electron microscope. They were observed to be small, isopolar, 3-colporate, the amb varies from subtriangular to circular, the shape from suboblate to oblate-spheroidal, and the surface from spiculate to reticulate. It is suggested, then, that the Solanaceae family is euripolinic, since the ornamentation of the exine is distinct among the genera. In Schwenchia it is reticulate and spiculate in Solanum. In order to separate these species based on pollen characters, a key was elaborated.